Conference Report: Functional Magnetic Resonance Imaging for Beginners – A Review of the fMRI Experience IV, 13–14 May 2002, Natcher Conference Center, National Institutes of Health, Bethesda, MD - Daniel Caggiano; Mateus Joffily (The Scientific World Journal)
The fourth fMRI Experience meeting was held at the Bethesda, Maryland campus of the National Institutes of Health on May 13th and 14th, 2002. The purpose of the meeting was to provide a platform for students working with functional magnetic resonance imaging (fMRI) to present their research to an international audience of peers. This year’s meeting featured special lectures from Dr. Leslie Ungerleider (“Imaging Mechanisms of Visual Attention”) and Dr. Daniel Weinberger (“Genetic Variation and fMRI Response”).